CD30+ Cutaneous Anaplastic Large-Cell Lymphoma of the Upper Eyelid: A Case Report - Stéphanie Olivier; Claire Dachelet; Ivan Theate; Isabelle Tromme; Marie Baeck (Karger Publishers, 2017)
CD30+ cutaneous anaplastic large-cell lymphoma is part of the CD30+ T-cell lymphoproliferative disorders. This type of lymphoma is in most cases indolent, with a high survival rate. We report the case of a 59-year-old patient with a 1-month lasting crusty lesion of the upper eyelid. Eyelid involvement is very uncommon, as the most frequent locations are the trunk and the limbs.